The Effect Of Value Clarification Technique On The Characteristics Of The Pancasila Student Profile In Class IV - Wahyudi, Theresia Putri; Tirtoni, Feri (Universitas Tanjungpura, 2024)
This study aims to determine the effect of the Value Clarifiacation Technique learning model in Pancasila subjects on the characteristics of the Pancasila student profile of class IV SDN Bareng Krajan II Krian District in the 2023/2024 school year. This type of research is a quasi-experimental research with a non-equivalent post test only control group design. The population of this study were all 133 students of SDN Bareng Krajan II. The samples of this study were class IV-A as the experimental group totaling 20 people and class IV-B students as the control group totaling 20 people. Data regarding students' characteristics were collected through a character instrument in the form of a questionnaire Data on student character was collected through. a character instrument in the form of a questionnaire consisting of 25 statements. Data analysis was conducted using descriptive analysis approach as well as inferential statistical analysis through independent sample t-test. Based on the results of the t-test calculation, it was found that the t-count value was 7.432, which was significantly greater than the t-table value of 2.024. The results imply a significant influence on the characteristics of the Pancasila learner profile between two groups of students who follow two different learning models, namely Value Clarification Technique and conventional learning models. This finding indicates that the Value Clarification Technique learning model has a positive impact on the development of Pancasila learner profile characteristics.